في نهر شط العرب latus (Houttuyn) Acanthopagrusبعض الملاحظات حول عمر ونمو سمكة الشانك - محمد سعد (University of Thi-Qar Journal of Science, 2010)
A 263 specimens of Acanthopagrus latus were collected from Shatt Al-Arab river from October 2008 to March 2009 to study age and growth of this species. The results revealed that length(L)weight(W) relationship was log W=-4.8512+3.0452 logTL , the length(L)- scale radius(S) related as : L=58.69+26.295S and Von Bertalanffy equation was Lt = 370.59(1-e67 -0.1993(t+2.7518) ) .